Phase separation behavior of polymer modified asphalt by molecular dynamics and phase field method: A review - Lin Chen; Ming Liang; Xin Wang; Xue Xin; Zhenchao Chen; Yuepeng Jiao; Jianjiang Wang; Yunfeng Zhang; Linping Su; Zhanyong Yao (Advanced Industrial and Engineering Polymer Research)
Abstracts: The research on the micro-compatibility mechanisms of polymer-modified asphalt is crucial for the field of road engineering. In-depth exploration and understanding in this area is highly challenged due to the current lack of sophistication in research tools and the lack of precision in research results. This paper reviews the research progress on phase separation in modified asphalt from the perspectives of phase field theory and molecular dynamics theory, while thoroughly analyzing the strengths and weaknesses of both approaches. Explore a new simulation method using phase field theory coupled with molecular dynamics parameters to more comprehensively and accurately model the phase separation behavior and characteristics of modified asphalt. This paper summarizes the simulation process of phase separation in modified asphalt based on phase field theory. By combining this with fluorescence microscopy experiments, it establishes and tracks the evolution of micro and mesoscopic phase states in modified asphalt over time. By utilizing molecular dynamics to construct molecular models of modified asphalt, this paper identifies key parameters, i.e. interaction parameters and migration coefficients, that control the phase field model of modified asphalt. It reveals the laws of phase behavior in modified asphalt from both micro and mesoscopic perspectives. By comparing fluorescence microscopy experiments and analyzing the degree of image overlap with image analysis technology, the consistency of simulation results can be demonstrated. This approach provides a theoretical reference for studying phase separation phenomena in the field of polymer science.